2021
DOI: 10.21468/scipostphys.10.5.099
|View full text |Cite
|
Sign up to set email alerts
|

The folded spin-1/2 XXZ model: II. Thermodynamics and hydrodynamics with a minimal set of charges

Abstract: We study the (dual) folded spin-1/2 XXZ model in the thermodynamic limit. We focus, in particular, on a class of ``local'' macrostates that includes Gibbs ensembles. We develop a thermodynamic Bethe Ansatz description and work out generalised hydrodynamics at the leading order. Remarkably, in the ballistic scaling limit the junction of two local macrostates results in a discontinuity in the profile of essentially any local observable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 49 publications
6
76
0
Order By: Relevance
“…The first, v n (λ), is naturally identified with the velocity of the excitations -accessible in TBA [85] -while the second, s n (λ), can be fixed by imposing the equality between the entanglement and the thermodynamic entropy in the stationary state [5]. All this is particularly simple for excitations on the stationary states (35) in Rule 54. Indeed, on these states there is only one species of excitations and λ can take only two values (λ ∈ {±}) (for further details see Paper I, the Supplemental Material of Ref.…”
Section: Von Neumann Entropy: Exact Confirmation Of the Quasiparticle Picturementioning
confidence: 99%
See 2 more Smart Citations
“…The first, v n (λ), is naturally identified with the velocity of the excitations -accessible in TBA [85] -while the second, s n (λ), can be fixed by imposing the equality between the entanglement and the thermodynamic entropy in the stationary state [5]. All this is particularly simple for excitations on the stationary states (35) in Rule 54. Indeed, on these states there is only one species of excitations and λ can take only two values (λ ∈ {±}) (for further details see Paper I, the Supplemental Material of Ref.…”
Section: Von Neumann Entropy: Exact Confirmation Of the Quasiparticle Picturementioning
confidence: 99%
“…which means that the quasiparticles cannot be though of as excitations on the stationary state (35), i.e. the state describing the expectation values of local observables at infinite times after the quench.…”
Section: Now We Note Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…The fixed-points given by the diagrams (54) generically exhibit bond dimension that grows exponentially with time t. However, as we argue below (and part of it was shown in [50]), in Rule 54 we can identify initial states and stationary states for which (54) reduce to an MPS with constant bond dimension χ = 3.…”
Section: A Solvable Case: Quantum Cellular Automaton Rule 54mentioning
confidence: 90%
“…An interesting route to achieve this goal has recently been pointed out in Refs. [50][51][52][53][54][55][56], which showed that in some special integrable models one can indeed access the full time evolution of local observables. In particular Ref.…”
Section: Introductionmentioning
confidence: 99%